Electrochemical investigation on the carbonate and phthalate-plasticized polyacrylonitrile based polymer electrolytes - Chong, W.G.; Osman, Z. (2014)
Polymer electrolytes consist of polyacrylonitrile (PAN), lithium tetrafluoroborate (LiBF4), ethylene carbonate (EC) and dimethyl phthalate (DMP) are prepared using solution casting method. The optimized composition gives high conductivity value of 1.08 x 10-2 S ern" at room temperature. The electrochemical properties of PAN-ECDMP- LiBF4 polymer electrolytes and the discharge characteristics of a Li/LiCo02 are investigated. The electrolytes show high electrochemical stability up to 4.4 V (versus Lt/Li).